A Rare Case With Multiple Dural Arteriovenous Fistulas: Case Report and Review of the Literature. Issue 3 (August 2015) - Wang, Kun; Yan, Zhang; Qi, Xuchen; Lin, Wei; Sun, Weijun
Abstract : We describe a rare case of multiple dural arteriovenous fistulas. A 20-year-old woman presented with a 3-day history of headache, vomiting, and seizure. A plain computed tomographic scan showed multiple high-density spots, and contrast-enhanced magnetic resonance imaging revealed diffusion restriction and multiple serpiginous flow voids in a wide area of the frontal, temporal, parietal, and occipital lobes. On digital subtraction angiogram, the dural arteriovenous fistulas (DAVFs) in the superior sagittal sinus were demonstrated on the bilateral common carotid artery angiographies. Its feeding arteries were the external carotid artery, superficial temporal artery, and middle meningeal artery. The DAVFs supplied by the bilateral ophthalmic artery with the cortical venous reflux were found by a selective angiogram of the bilateral external carotid artery. Digital subtraction angiogram also demonstrated the DAVFs with the vein of Galen, supplied by the bilateral middle cerebral artery and posterior cerebral artery. For the complication of disease and economic reason, the patient was finally discharged from the hospital without treatment. The history, neuroimaging, and histopathology of this patient are discussed.